Comparative analysis of swimming techniques in gymnasiums and open water swimming techniques in swimming - Suo, J. (Open Access Library Journal, 2023)
With the rapid development of our country`s economy and the continuous prevalence of national fitness, more and more swimming enthusiasts and professional swimmers participate in open water swimming and enjoy this challenging project. The swimming events in our country`s venues are basically ranked in the leading position in the world, and there are also many outstanding athletes such as Wang Shun, Sun Yang, Zhang Yufei and so on. However, there is still a certain gap between the level of open water swimming in China and the level of swimming in venues. Swimming in open water is carried out in open water. Due to external uncontrollable environmental factors, such as Climate, water quality, water temperature, water flow direction, etc., the environmental changes during the swimming process are unpredictable, and the risk factor is relatively large. Therefore, the technical requirements for athletes are also quite different from those of swimming in ordinary venues. This paper compares and analyzes open water swimming techniques and swimming techniques in venues by using literature, comparative analysis, and video observation methods. The research results show that: 1) in the case of the 1500-meter freestyle at the same distance, swimming in ordinary venues will have the action of rolling and kicking the wall, which reduces the distance for athletes in the process of swimming. However, open water swimming does not have any auxiliary actions after starting, and coupled with the influence of uncontrollable external environment and other factors, open water freestyle swimming takes longer than ordinary swimming pool freestyle swimming. 2) Open water swimming and swimming in ordinary venues are divided into three stages: departure, en route and sprint. However, judging from the comparison of the final results of the two, the speed of open water swimming fluctuates greatly during the swimming process, which is also related to the uncontrollable external environment. The swimming speed in the venue is relatively uniform. The tactics are arranged in advance to carry out the competition, so the tactical allocation of open water swimming and swimming in the venue is different. 3) Swimming in ordinary venues is carried out under relatively stable conditions, so athletes will not be affected by external influences and change their movement skills during swimming. The actual effect is relatively stable and the fluctuation is small. 4) Since the open waters have not been treated and the visibility is low, athletes should use "head-up swimming" to observe the floats and so on to control the direction of their swimming when swimming in the open waters. Ordinary swimming pools have undergone water treatment and have high visibility. When swimming in ordinary swimming pools, athletes do not need to deliberately observe the direction of swimming. Therefore, swimming in open water consumes more energy than swimming in ordinary venues.